1992
DOI: 10.1038/sc.1992.109
|View full text |Cite
|
Sign up to set email alerts
|

The older adult with a spinal cord injury

Abstract: Sixty-two consecutive acute spinal cord injury (SCI) patients who were aged 55 years or older were studied and compared to 296 SCI patients of age less than 55 years. Compared to younger patients, the older group had significantly more females (29%), preexisting medical conditions (87%), associated injuries (55%), incomplete quadriplegic patients (63%), and persons whose injuries resulted from falls (53%). There were no differences between groups in frequency of ventilator use, occurrence of medical complicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
2
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 14 publications
(5 reference statements)
3
36
2
1
Order By: Relevance
“…With regard to LOS in our series, older patients had a significantly shorter LOS, a finding similar to Roth et al, 13 but opposite to Cifu's data 7 on paraplegic subjects. LOS could be influenced by a series of factors: the completeness of lesion (a high number of patients with incomplete tetraplegia in older group could justify the shorter LOS of this group); the higher frequency of comorbidities in older patients could interfere with the rehabilitation process, which could in turn affect the length of stay; 1 the discharge disposition and the increase likelihood of institutionalisation of older patients, which could affect the length of stay for awaiting placement.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…With regard to LOS in our series, older patients had a significantly shorter LOS, a finding similar to Roth et al, 13 but opposite to Cifu's data 7 on paraplegic subjects. LOS could be influenced by a series of factors: the completeness of lesion (a high number of patients with incomplete tetraplegia in older group could justify the shorter LOS of this group); the higher frequency of comorbidities in older patients could interfere with the rehabilitation process, which could in turn affect the length of stay; 1 the discharge disposition and the increase likelihood of institutionalisation of older patients, which could affect the length of stay for awaiting placement.…”
Section: Discussioncontrasting
confidence: 52%
“…The choice of age 50 years, although arbitrary, was made on the basis of previous reports. [12][13][14] Only patients who had the cognitive ability to participate in the rehabilitation programme were included. Whenever a patient was discharged or transferred for more than 3 weeks, the readmission was considered a second admission and the patient was excluded.…”
Section: Subjectsmentioning
confidence: 99%
“…15 The same age criterion has been used previously in other studies. 9,15,16 Forty (20.8%) subjects were aged 55 ± 85, the mean age of this group was 66.3 years (SD=7.4). One hundred and ®fty-two (79.2%) subjects were aged 16 ± 54, the mean age of this group was 34.0 years (SD=10.6).…”
Section: Methodsmentioning
confidence: 99%
“…However, the evidence is equivocal. Roth, Lovell, Heinemann, Lee and Yarkony 9 report no di erences in the frequency of complications following SCI or the requirement for mechanical ventilation between older and younger adult age groups. Furthermore, Krause,10 in a study to investigate ageing after SCI, found that acquiring a SCI at an older age was associated with the reduced risk of developing several conditions.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation